Body Mass Index, Hemoglobin levels and Grade-Point Average for Public Health Students: Cross Sectional Study - Syamsul Alam; Sukfitrianty Syahrir; Maesarah Yasin; Aswadi Aswadi (Journal of Public Health and Pharmacy, 2025)
Introduction: Poor nutrition can disrupt a child's motivation, ability to train, and his ability to learn. This will affect children's learning achievement. The first-year students following the lecture process with the block system have an average GPA lower than students who use the lecture system block two to three years. The aim to find out the nutritional status and the college student's achievement index who take the block system learning method in the learning environment of the public health department UIN Alauddin Makassar. Methods: The participants were 88 students from the public health department of UIN Alauddin Makassar with the Cross-Sectional approach method. The research data was obtained by measuring anthropometry based on BW / TB, measurement of hemoglobin, and student achievement index. Data were analyzed by the chi-square test at p-value <0.05. Results: The results showed that the analysis of BMI based on indicators of weight and height measurements obtained the normal nutritional status of students only 40.9%, nutritional status underweight category as much as 35.2% and overweight or overweight as much as 23.9%. The results of hemoglobin examination (g / dl) showed that respondents had anemia which was as much as 71.6%, which was not anemic 28.4%. The results showed that there was no relationship between the BMI with the learning achievement of students who took classes with the block system in health study programs, P-value = 0.902. P-value = 0.001, which shows that there is a significant relationship between anemia status and achievement index obtained during the 2 semesters of lectures that have been followed. Conclusion: Anemia is one of the nutritional problems that can affect student learning achievement, so students can improve consumption patterns that affect hemoglobin.